Digital Power Exchange Option Pricing under Non-Affine Stochastic Volatility Models - Zhang, Jingting; Zhang, Jingjing (Journal of Global Economy, Business and Finance, 2025)
This paper investigates the pricing of digital power exchange options under a non-affine stochastic volatility model. We first derive an approximate characteristic function for the logarithmic price distribution of underlying assets through perturbation analysis of partial differential equations. Subsequently, the analytical expression for digital power exchange options is obtained by employing Fourier transform and its inverse transformation.